Black phosphorene-cellulose nanofiber hybrid paper as flexible heat spreader. (13th September 2021) - Wei, Xianzhe; Song, Guichen; Wang, Bo; Li, Maohua; Qin, Yue; Li, Linhong; Cui, Junfeng; Cai, Tao; Dai, Wen; Lin, Cheng-Te; Jiang, Nan; Pan, Zhongbin; et al.
Abstract: In this work, black phosphorene (BP) was exfoliated by solvent exfoliation of black phosphorus powders in N-methyl pyrrolidone. The BP-cellulose nanofiber (CNF) paper was prepared from the solution containing BP and CNF by vacuum filtrating. The as-prepared BP-CNF paper has a 'brick-and-mortar' structure. The BP-CNF paper has a high in-plane thermal conductivity of 22.3 W m −1 K −1 at room temperature, benefiting from the thermal transition pathways constructed by the 'brick-and-mortar' structure. In addition, the BP-CNF possesses an excellent flexibility. Our results in this work demonstrate that BP has a great potential in the application of thermal management material.